Simulation and Experimental Study of Ball Position Control at Biaxial Platform using State Space Approach - Sumega, Martin; Struharnansky, Lubos; Gorel, Lukas; Pacha, Matej (Communications - Scientific letters of the University of Zilina, 2018)
Ball on plate platform is a great tool for testing of various control techniques. This study provides a detailed design and comparison of three control structures for automatic stabilization of the ball´s location on plate and ball trajectory tracking. Namely PD controller, state space feedback and state space observer with state space feedback. All three methods are designed and practically compared. All structures have a common feature. It is the methodology for calculating the parameters of the controllers. Ball - on - plate mathematical model derived by Newton´s method and DC motor position loop control are also part of this article. For the authors of this article, this study is an opportunity to create an educative setup to explain the principles of basic control system for non - technical person and offers motivation to future students.